Momento de Irrigar a Cultura de Amendoim Utilizando a Termometria a Infravermelho - Turco, José Eduardo Pitelli [UNESP]; Vieira, Ana Carla Nogueira Tobias [UNESP] (Sociedade Brasileira de Meteorologia, 2021)
The use of water stress indexes in the developmental phases of the crop can be an essential tool for irrigation control. The aim of this study was to determine the ideal time to irrigate a peanut crop, using a water stress index found using infrared thermometry. The research was developed in the experimental area of the Department of Rural Engineering of FCAV / UNESP, Jaboticabal-SP, located at 22°15’22” S, 48°18’58” W, and altitude of 575 m, in an “Hydrographic Basin” (0%, 20% and 40%) and solar exposures (North, South, East and West), under induced water deficit. The soil of the experimental area is LE1, Red-Dark, eutrophic, A moderate, kaolinite, hypoferric, clayey texture, smooth undulating relief (Eutrustox). Water stress level was determined by measuring the temperatures of the vegetation cover and the ambient air. Watering was carried out using a drip irrigation system. The results indicate that the time of irrigation differs for each stage of development of the peanut, in a range between 1.3 °C and 3.3 °C. The area maintained in the field capacity obtained lower water stress index (-1.4°C).

O uso de índices de estresse hídrico nas fases de desenvolvimento da cultura pode atuar como uma ferramenta essencial no manejo da irrigação. Objetivou-se com este trabalho determinar o momento ideal de irrigar a cultura do amendoim, por meio de índices de estresse hídrico utilizando-se a termometria a infravermelho. A pesquisa foi desenvolvida na área experimental do Departamento de Engenharia Rural da FCAV/UNESP, Jaboticabal-SP, situada a 22°15’22” S, 48°18’58” W, e altitude de 575 m, em uma “Bacia Hidrográfica Experimental”, utilizando superfícies com diferentes declividades (0%, 20% e 40%) e exposições solares (Norte, Sul, Leste e Oeste), sob déficit hídrico induzido. O solo da área experimental é o LE1, Vermelho-Escuro, eutrófico, A moderado, caulinítico, hipoférrico, textura argilosa, relevo suave ondulado (Eutrustox). O índice de estresse hídrico foi determinado por meio da medição da temperatura da cobertura vegetal e do ar ambiente. A rega foi realizada utilizando-se sistema de irrigação por gotejamento. Os resultados indicam que o momento de irrigar difere para cada fase de desenvolvimento do amendoim, em uma faixa entre 1,3 °C até 3,3 °C. A superfície mantida na capacidade de campo obteve menor índice de estresse hídrico (-1,4 °C).
The Timeto Irrigate a Peanut Crop Using Infrared Thermometry
Keywords: water and soil management; water stress; sloping surfaces; manejo de água e solo; déficit hídrico; superfícies inclinadas